The Of Business Performance on Tourism Empowerment Of Tanjung Bira Bulukumba District - Awalia, Yusniharti; Suyuti, Muh Rizal; Rivai, Andi Muhammad (Universitas Negeri Makassar, 2024)
This study aims to determine how much influence business performance has on empowering Tanjung Bira tourism in Bulukumba Regency. To achieve this goal, researchers use indicators to measure these variables. In the variable business performance indicators used are increased sales, increased profits and satisfactory growth. The tourism empowerment variable uses involvement, trust, and communication indicators. This study uses quantitative research. Data collection techniques carried out are through observation and questionnaires. The population in this study were UMKM business actors in the Bira beach area of Bulukumba Regency with a total of 50 respondents. The sampling technique used in this study was the Nonprobability Sampling Technique by collecting sample data using a questionnaire. Data obtained from research results were processed using data analysis and SPSS version 25 application consisting of validity and reliability tests, descriptive statistical data analysis techniques and inferential statistical analysis. The results of this study indicate that the indicators used for each variable of business performance and tourism empowerment are in the sufficient category. Based on the test of the determinant coefficient between the two variables, there is an effect of 58.0%. Based on the simple linear regression coefficient shows a positive value, so it can be said that the direction of the influence of variable X on Y is positive. So, it can be concluded that there is a significant positive influence between business performance and tourism empowerment.Keywords: Business Performance, Tourism Empowerment.